BENEFICIAL EFFECT OF VITAMIN D ON HIGH-FAT DIET-INDUCED OBESITY IN WISTAR RATS - Verma, Ashima; Goyal, Amit; Kaur, Ramneet; Kamboj, Anjoo; Jain, Upendra K (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: The aim of the present study was to investigate the antiobesity effects of vitamin D (VD) on high-fat diet (HFD)-induced obesity in Wistar rats. Methods: In the present study, male Wistar rats were selected after 4 weeks feeding of HFD and then treated with different doses of VD (2.5-10 mcg/kg/day, p.o.o.d.) for 6 weeks along with HFD. Orlistat (30 mg/kg/day, p.o.o.d.), which is a lipase inhibitor a standard drug for obesity was used as a standard control in the present study. The effects of these treatments on body weight parameters, feed intake (Kcal), weight and size of fat pads, levels of serum glucose, triglycerides (TGs), total cholesterol (TC), high-density lipoproteins (HDL), and low-density lipoprotein (LDL) were analyzed. Results: Treatment with VD (2.5-10 mcg/kg/day, p.o.o.d.) produced significant dose-dependent decrease (p<0.05) in body weight parameters, feed intake (Kcal), weight and size of fat pads, levels of serum glucose, TGs, TC, and LDL as compared to HFD group. Moreover, the level of serum HDLs was increased as compared to HFD group. Conclusions: VD treatment ameliorated established obesity and associated biochemical consequences. The results suggest that administration of VD can inhibit the development of obesity and associated metabolic consequences in HFD-induced obesity. Keywords: Obesity, Vitamin D, High-fat diet.